UPAYA MENINGKATKAN AKTIVITAS BELAJAR SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN PROBLEM POSING TIPE PRE SOLUTION POSING DI SMP NEGERI 15 KOTA BENGKULU - Agustin, Mely; Yensy, Nurul Astuty; Rusdi, Rusdi (JP2MS, 2017)
This research aims to found out how to applyed Problem Posing Model Pre solution Posing Type in learning so that there were increased students learning activity. The design of this  research was Classroom Action Research (PTK). The subjects of this research were students of class VIII B Junior High school 15 Bengkulu City in academic years 2016/2017. The instrument of this research was observated sheet of student learning activity. The indicators of the success of the actions in this research were student learning activities in active criteria (in result students learning activitiy interval contain  ). The result of the research saw that there was an increased of students' learning activity by giving motivation to the students to be active in the learning and presentation activities and gave additional value for the students who dare to express their opinions in front of the class and actively inquire during the presentation. Increased student activity can be seen from the average score on the observation sheets of student learning activities cycle I to cycle III in a row: 15,17 (criteria less active); 20.84 (fairly active criteria); 25.83 (active criteria). Keywords: Problem Posing Model Pre solution Posing Type; Learning Activity.